(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Raw materials and materials form a big part of the cost price of the end product. At the same time, the deviations from the requirements put forward to them impede the manufacturing processes, lead to additional expenditure for elimination and compensation of the discrepancies of the raw materials delivered, serious losses and lost profit for the manufacturer. The provision of raw materials and materials of constant quality is not always achievable and that is why it is necessary to assess the deviations from the optimum requirements and to determine what it costs to us to eliminate / compensate them and at minimum expenditure at that. In the report, methods for assessment of suppliers of urea-formaldehyde resin are presented. They reflect the relationship between manufacturing and financial indices (price, expenditure, lost profit) when assessing the losses from deviation in the raw materials quality.